2010
DOI: 10.3991/ijoe.v6i1.1131
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of Remote Laboratories in Control Engineering Education

Abstract: Abstract-Remote laboratories have made significant progress during last few years. Their integration in engineering education helps solve many logistical difficulties inherent in conventional labs. In control engineering education, shifting from hands-on experience to remote experimentation completely modifies the learning environment. Also, factors that can compromise the effectiveness of learning outcomes need to be carefully considered. This short paper discusses a number of pedagogical limitations intrinsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Virtual based learning environments have been shown to engage learners, and facilitate classroom instruction in several domains (Przybylski et al, 2012). However, in computing education, studies reported mixed results; some studies were in favor of virtualization Zhu (2015); Xu et al (2014); Plass et al (2012); Gaspar et al (2008) while other studies highlighted the drawbacks of using virtualization, namely; they did not allow collaborative learning, apprehending that it might have negative effects on students' motivation (Aliane et al, 2010) that they offered little benefit to students, and added unnecessary abstraction layer to the learning process (Pan, 2010). Given such contradictory views on the impact of virtualization on computer network learning, this two-group quasiexperimental study has attempted to investigate the impact of a virtual learning environment, namely, OPNET Networking simulator, on students' learning and motivation.…”
Section: Introductionmentioning
confidence: 99%
“…Virtual based learning environments have been shown to engage learners, and facilitate classroom instruction in several domains (Przybylski et al, 2012). However, in computing education, studies reported mixed results; some studies were in favor of virtualization Zhu (2015); Xu et al (2014); Plass et al (2012); Gaspar et al (2008) while other studies highlighted the drawbacks of using virtualization, namely; they did not allow collaborative learning, apprehending that it might have negative effects on students' motivation (Aliane et al, 2010) that they offered little benefit to students, and added unnecessary abstraction layer to the learning process (Pan, 2010). Given such contradictory views on the impact of virtualization on computer network learning, this two-group quasiexperimental study has attempted to investigate the impact of a virtual learning environment, namely, OPNET Networking simulator, on students' learning and motivation.…”
Section: Introductionmentioning
confidence: 99%
“…To accommodate new experiments one has to redesign the system. In this respect, some of the limitations of remote laboratories are reported some researchers [35]. c) Readily available commercial products: In recent years both the hardware and software technologies has been developed extensively, which has enabled the Internet accessible experiment designers to come up with more powerful systems that was not possible in the past.…”
Section: A What Are the Issuesmentioning
confidence: 99%
“…Most of these examples offer the possibility of working on either a simulated version of a physical process or a real device located at the universities laboratories. However, such platforms have certain limitations [16] that should also be enhanced to take into account the advantages of augmented reality instead of showing only visual feedback by video stream, specifically:…”
Section: Augmented Reality In Remote Experimentationmentioning
confidence: 99%